Explaining and Evaluating the Understanding of Divine Attributes from the Perspective of Mirza Mahdi Esfahani - Mahdi Azadparvar (آموزه‌‌های فلسفه اسلامي)
The issue of knowing the divine attributes and their semantics is one of the most important and controversial issues in the discussion of knowing the Almighty God. Mirza Mahdi Esfahani, by emphasizing verses and hadiths (traditions), seeks to express a special type of negative theology, which is different from other words of those who believe in negative theology, such as Ibn Maimon (Maimonides, Moses ben Maimon) and Qadi Sa’id. In his view, God has attributes, and these attributes are established equivocally (homonymous). The intellect of human beings cannot also know the divine attributes due to the inconsistency between the Creator and the creature, and the description of God to human notions, concepts and knowledge is not correct, but it is God who introduces his attributes to human beings and for this reason, this quotation of this theory does not lead to the cessation of the knowledge of God’s attributes. By explaining and analyzing this theory, it becomes clear that this theory actually leads to the cessation of the intellect in understanding the knowledge of divine attributes.